Performance evaluation of a standalone hybrid microgrid for a rural community using various dispatch strategies. (2nd February 2023) - Garg, Vijay Kumar; Sharma, Sudhir
Distributed energy sources prove to be a viable alternative for electricity in rural/remote areas. In this paper, the performance of a standalone hybrid microgrid comprising of solar photovoltaic (PV), diesel generator (DG), and battery energy storage system (BESS) has been evaluated for a small rural community. The overall aim is to propose sustainable, economical and reliable electricity supply in rural/remote areas. The optimum sizing of various units has been evaluated using hybrid optimisations multiple energy resources (HOMER) simulations with four dispatch strategies, i.e., load following, cycle charging, combine dispatch, and predictive dispatch. The outcomes show that the PV-DG-BESS system is an optimal solution based on net present cost (NPC) and cost of energy (COE) parameters under a predictive dispatch strategy. The sustainability of the optimum hybrid microgrid has been evaluated using sensitivity analysis using various input parameters.